017 Year 1 performance of adveva® programme for patients taking cladribine tablets for relapsing-remitting multiple sclerosis. Issue 6 (27th May 2022) - Morgan, Kate; Lott, Nadine; Lyons, Marco
Abstract : Background: The nurse-led, telephone-based adveva® programme - including dosing advice, appoint- ment reminders and a home-based phlebotomy service - supports patients with relapsing-remitting multiple sclerosis (RRMS) in taking cladribine tablets (CT) as prescribed (the full first year cumulative dose of 1.75 mg/kg). We report year 1 results of the adveva® progamme for patients with highly active RRMS taking CT. Methods: Aggregated and anonymised telephone conversation records were reviewed between December 2017 and August 2018. Patient-reported adherence, plus basic and additional support data, were analysed. Results: 262 patients were registered with adveva® and 133 were included in this assessment as they self- reported to have completed treatment in year 1 at the time of assessment. 130 (98%) patients completed their first-year course as prescribed (the remaining 3 patients received the required dose at a different time interval to that recommended). 22 (17%) patients required additional support during their treatment days, included advice on treatment/dosing/adverse events. Conclusions: All 133 patients self-reported that they achieved the required CT dose in year 1; the adveva® programme was of particular value to patients requiring additional support. This is the first report in a post- approval and real-world setting suggesting the majority of patients find CT simple-to-take. kate.morgan@merckgroup.com